Learning Logic Gates Using Augmented Reality - Nurul Hidayah Rahani; Aldrin Aran Bilong; Muhammad Rafiq Mat Suruji; Ismail Yusuf Panessai (International Journal of Multimedia and Recent Innovation, 2020)
This research is important to enhance students understanding and learning performance in Computer Organization and Architecture subject especially in logic gate circuit topic as student also can improve their knowledge and usage in new technology like AR. The appropriate methodology chosen in development of this research is ADDIE model which is consists of five phases. The application were evaluated by the student who take Computer Organization and Architecture subject in Sultan Idris Education University. By using ADDIE model as its methodology, the planning of this mobile application was successfully proceeding smoothly starting from the analysis phase until evaluation phase. The details gained from the phase of evaluation will be explained through the next chapter of this research. Overall from this research, the AR-LoGates Apps has shown that it is a necessary product by receiving a good reception from students. The results proved that AR-LoGates application can help students in learning especially in easy to understanding the logic gate topic and make the learning become interesting way.